Farmers’ perceptions about exotic multipurpose fodder trees and constraints to their adoption - Mekoya, A.; Oosting, Simon J.; Fernández Rivera, S.; Zijpp, A.J. van der (Springer, 2008)
Many organizations in Ethiopia have for many years promoted exotic multipurpose fodder trees (EMPFT) for livestock feed and soil improvement. Despite the apparent benefits, the number of farmers planting these trees was low. The objectives were to elucidate farmers’ perceptions about their use value, management practices and constraints to adoption in three districts representing annual (one wheat-based and one teff-based) and perennial (coffee- based) crop-livestock systems in the Ethiopian highlands. Data were collected from 235 farm households. Most farmers (95.3%) had awareness of EMPFTs and the principal information sources were development agents (75.3%). Over half of the farmers were motivated to plant EMPFTs for feed value. Motivation for other purposes depended on cropping system, vegetation cover and availability of alternative local fodder trees in the area. Farmers had positive perceptions about EMPFTs for their feed value and contribution to soil conservation. Current adopters had a mean number of 587 (SE ± 84 EMPFTs per farm. Major constraints to adoption of EMPFTs were agronomic problems, low multipurpose value, and land shortage. Majority of farmers (89.8%) were interested to either continue or begin fodder tree development. Of the interested respondents, 44.5% preferred local fodder trees whereas 55.5% preferred EMPFTs. We conclude that farmers are aware of use values of EMPFTs while perceived constraints suggest that introduction of EMPFTs need consideration of farmers multiple criteria, but also awareness of feeding fodder trees and resource availability. Moreover, current development approaches have to recognize the importance of involving the end-users at all stages through participatory approaches to enhance adoption.